2018
DOI: 10.1080/15568318.2018.1481243
|View full text |Cite
|
Sign up to set email alerts
|

A review of spatial localization methodologies for the electric vehicle charging infrastructure

Abstract: With view to the high share of the transport sector in total energy consumption, e-mobility should play an important role within the transition of the energy systems. Policymakers in several countries consider electric vehicles (EV) as an alternative to fossil-fueled vehicles. In order to allow for the development of EV, the charging infrastructure has to be set up at locations with high charging potential, identified by means of various criteria such as demand density or trip length. Many methodologies for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 121 publications
(170 reference statements)
0
52
0
2
Order By: Relevance
“…Pagany et al [22] gave a broad and systematic overview of publications in the domain of CS localization for EVs. The review categorized 661 studies based on their structure (user, destination, or route orientation), overarching objectives (like demand density, trip length, or queuing), and data sources (statistics, measured travel data, simulations or surveys) and discussed the advantages and limitations of the applied data and methods.…”
Section: State Of the Art Of Cs Location Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pagany et al [22] gave a broad and systematic overview of publications in the domain of CS localization for EVs. The review categorized 661 studies based on their structure (user, destination, or route orientation), overarching objectives (like demand density, trip length, or queuing), and data sources (statistics, measured travel data, simulations or surveys) and discussed the advantages and limitations of the applied data and methods.…”
Section: State Of the Art Of Cs Location Modelsmentioning
confidence: 99%
“…Pagany et al [22] concluded that a more integrated process should be the aim of further research on CS localization. Based on this, our study pursues a more holistic CS localization model, including EV drivers' dwelling times and destinations as well as the points of interest (POIs) as the model's key aspects.…”
Section: State Of the Art Of Cs Location Modelsmentioning
confidence: 99%
“…In the transportation system, EV infrastructure resources, such as charging stations, parking lots, and roads, represent the supply side that electric vehicle owners (as the demand side) will take advantage of [7]. There are many dynamic factors (location, time, and scale) that could affect EV infrastructure resources and restrict the travel demand by EV drivers [8].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the application of LBS big data in the study of EV mobility or travel behavior is under exploration and mostly focuses on planning public charging stations. For example, Tu et al used the GPS data of EV ride-hailing groups to estimate charging demand [15]; Weldon et al used the GPS-tracked EV fleet in Ireland to support charging station planning and Pedge et al discussed the available data sources for charging behavior modelling [40,41]. Distinguishing between EV users and non-EV users and establishing an acceptable data security mechanism also become challenging when using these types of data.…”
Section: Introductionmentioning
confidence: 99%